Spermatological characters of the digenean Lecithostaphylus retroflexus (Molin, 1859) (Microphalloidea: Zoogonidae), a parasite of the teleost fish Belone belone gracilis. Issue 4 (August 2015) - Kacem, H.; Ndiaye, P.I.; Neifar, L.; Torres, J.; Miquel, J.
Highlights The ultrastructural organization of the spermatozoon of the digenean Lecithostaphylus retroflexus (Microphalloidea: Zoogonidae) was described. Indeed, alive digeneans were collected from Belone belone gracilis (Teleostei: Belonidae), caught from the Gulf of Gabès in Chebba (Tunisia). The mature spermatozoon of L. retroflexus exhibits two axonemes of different lengths with the 9 + '1' Trepaxonematan pattern, a nucleus, two mitochondria, two bundles of parallel cortical microtubules and granules of glycogen. Additionally, the spermatozoon of L. retroflexus shows type 2 of the external ornamentation of Quilichini et al. (2011), spine-like bodies and a continuous and submembranous layer of parallel cortical microtubules surrounding the axonemes at their anterior end. Moreover, the morphology of the posterior spermatozoon extremity in L. retroflexus corresponds to the fasciolidean type of Quilichini et al. (2010).